1985
DOI: 10.1056/nejm198503283121302
|View full text |Cite
|
Sign up to set email alerts
|

Diet and 20-Year Mortality from Coronary Heart Disease

Abstract: In a prospective epidemiologic study of 1001 middle-aged men, we examined the relation between dietary information collected approximately 20 years ago and subsequent mortality from coronary heart disease. The men were initially enrolled in three cohorts: one of men born and living in Ireland, another of those born in Ireland who had emigrated to Boston, and the third of those born in the Boston area of Irish immigrants. There were no differences in mortality from coronary heart disease among the three cohorts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
182
2
10

Year Published

1988
1988
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 442 publications
(219 citation statements)
references
References 27 publications
8
182
2
10
Order By: Relevance
“…This study confirms in a Southern European population the inverse association found in studies from Northern Europe and the USA (Bolton-Smith et al, 1992; Burr & Sweetnam, 1982;Fehily et al, 1993;Humble et al, 1993;Khaw & BarrettConnor, 1987;Kromhout et al, 1982;Kushi et al, 1985;Morris et al, 1977;Pietinen et al, 1996;Rimm et al, 1996;Wolk et al, 1999). Only a few studies, however, adjusted for energy intake and presented data separately for different types and sources of fiber.…”
Section: Fiber and Myocardial Infarction E Negri Et Alsupporting
confidence: 81%
See 2 more Smart Citations
“…This study confirms in a Southern European population the inverse association found in studies from Northern Europe and the USA (Bolton-Smith et al, 1992; Burr & Sweetnam, 1982;Fehily et al, 1993;Humble et al, 1993;Khaw & BarrettConnor, 1987;Kromhout et al, 1982;Kushi et al, 1985;Morris et al, 1977;Pietinen et al, 1996;Rimm et al, 1996;Wolk et al, 1999). Only a few studies, however, adjusted for energy intake and presented data separately for different types and sources of fiber.…”
Section: Fiber and Myocardial Infarction E Negri Et Alsupporting
confidence: 81%
“…Several, mostly prospective, epidemiological studies, (Bolton-Smith et al, 1992;Burr & Sweetnam, 1982;Fehily et al, 1993;Humble et al, 1993;Khaw & Barrett-Connor, 1987;Kromhout et al, 1982;Kushi et al, 1985;Morris et al, 1977;Pietinen et al, 1996;Rimm et al, 1996;Wolk et al, 1999) have investigated the relation between fiber intake and risk of acute myocardial infarction (AMI) or cardiovascular disease in general. Most have found significant inverse associations, although only a few have presented estimates adjusted for energy intake and separately for different types and sources of fiber (Kushi et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ireland also has a huge migrant related diaspora, the health status of which, has, paradoxically, been better studied in some instances than those who remained at home. (Burvil, McCall, Woodings, & Stenhouse, 1983;Wild & McKeigue, 1997;Harrison, Carrhill, & Sutton, 1993;Kushi, Lew, Stare, & Ellison, 1985;Abbotts, Williams, Ford, Hunt, & West, 1999;Harding & Balarajan, 1996, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…In regard of cardiovascular disease risk, many short-term studies have suggested a dose-dependent hypertriglyceridemic effect for dietary carbohydrates and sucrose (Parks and Hellerstein, 2000). However, longer observational studies have not provided evidence of increased risk of coronary heart disease (CHD) (Kushi et al, 1985;Liu et al, 2000). On the other hand, in a recent study weight gain and risk of type II diabetes were related to consumption of sugar-sweetened beverages in women (Schulze et al, 2004).…”
Section: Introductionmentioning
confidence: 99%